THE SOCIAL STRATA SYSTEM AND ITS IMPACT ON WOMEN'S SOCIAL ROLE IN THE PROPHETIC AND CALIPH ERA (610-661 AD) - Masruri, Muhammad Hadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The outlook against women defining her role in the domestic sector still prevails to this day in Islamic society, especially in Middle East countries where some consider that Islam is against women's role in the public sector. Therefore, this study concludes that the expansion of Islamic empire and the conquest of new lands in the caliphate era, especially in the era of 'Uthmân ibn 'Affân has affected some. For example the uncontrollably rise of Jawârî in the center of Islamic government Medina, conquering new territories, the impossibility of identifying women and other neighbors, the limited activity for women in domestic sector, as well as the Prophet PBUH’s duty to marry his wives to reduce the women’s role in that era. This study attempts to prove that social class system in society has significant impact on social role played by Arab women at that time. It also affects the formation of social relation pattern for women. The higher the social classes of women, the more freedom for aristocratic women Chandeliers in playing a keyrole in many social activities, including intervention in war and expropriation, as well as enjoying the high degree of access to human right in social role that other women cannot enjoy. This is what happened in the era of the Prophet and Caliph.